Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1002/adfm.201505538
|View full text |Cite
|
Sign up to set email alerts
|

All‐Solution‐Processed Random Si Nanopyramids for Excellent Light Trapping in Ultrathin Solar Cells

Abstract: Si nanopyramids have been suggested as one of the most promising Si nanostructures to realize high-efficient ultrathin solar cells or photodetectors due to their low surface area enhancement and outstanding ability to enhance light absorption. However, the present techniques to fabricate Si nanopyramids are either complex or expensive. In parallel, disordered nanostructures are believed to be extremely effective to realize broadband light trapping for solar cells. Here, a simple and cost-effective method is pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 34 publications
1
35
0
Order By: Relevance
“…When irradiated by laser, the system with suitable thickness presents a conspicuous LPE with a high sensitivity (maximum reaches 157.9 mV·mm −1 ) as shown in Figure b. This surface morphologies of random nanopyramids bring a low surface recombination and more optical resonance modes, which cause a greater light harvesting (shown in Figure c) and benefit the performance of LPE a lot . The reference also displays a simulation of this system whose result is consistent with above statements as well.…”
Section: Lateral Photovoltaic Effectsupporting
confidence: 79%
“…When irradiated by laser, the system with suitable thickness presents a conspicuous LPE with a high sensitivity (maximum reaches 157.9 mV·mm −1 ) as shown in Figure b. This surface morphologies of random nanopyramids bring a low surface recombination and more optical resonance modes, which cause a greater light harvesting (shown in Figure c) and benefit the performance of LPE a lot . The reference also displays a simulation of this system whose result is consistent with above statements as well.…”
Section: Lateral Photovoltaic Effectsupporting
confidence: 79%
“…6. It can be seen that in the short wavelength region (e.g., 0.3 μm), nanostructure provide Mie scattering resonance to enhance the absorption performance [52], [53], but strong surface reflection limits the increase of absorption. In the mid-band (e.g., 0.5 μm), besides the weak Mei scattering resonance and F-P resonance, the first-order diffraction of nanostructure also provides a strong optical waveguide mode, which greatly improves the absorption capacity of c-Si [54], [55].…”
Section: Resultsmentioning
confidence: 99%
“…From the image, one can also see that the produced micro-pyramid array is a randomly sized pyramid array surface. This feature may be an advantage, as mentioned in [15], a random-sized pyramid array surface can have better light collection efficiency than a planar and single-sized pyramid array surface over a wide wavelength range. The average spacing between the micro-pyramids is about 2.8 µm, and the average width of the micro-pyramids at the base is about 1.4 µm.…”
Section: Characterization Of the Developed Substratesmentioning
confidence: 95%
“…An anisotropic wet chemical etch is typically utilized to form a micro-sized pyramidal structure as a light-harvesting structure using different etch rates of silicon crystals at <100> and <111> surfaces [14]. It has been shown that a randomly sized pyramid array surface can have better light-harvesting efficiency and therefore a better absorption coefficient than planar and single sized pyramid array surfaces [15]. In some SERS studies [7][8][9], It has been proven that the Si pyramids can increase the amount of the hot spots by providing large surface area and create strong local electric field [9].…”
Section: Introductionmentioning
confidence: 99%